Optimization of Ferry Ship Design on the Bombana - Tanjung Pising - Baubau Route - Dian Andalan Pertiwi (West Science Interdisciplinary Studies, 2023)
The objective of this research is to get the optimal ship dimension for the Bombana - Tanjung Pising - Baubau crossing route. This research uses a linear programming optimization method. By identifying problems and mismatches of ships operating with the main objective of ferry transportation, and determining the objective function of optimization. Then determine the aspects of ship design that are adjusted to the characteristics of the ferry based on optimization constraints, namely demand conditions, oceanography and infrastructure. The direction of optimization is more emphasized on increasing the speed and effectiveness of greater loading capacity on passenger and vehicle. The results have been obtained in the form of the optimal principal dimension of the ship for the Bombana - Tanjung Pising - Baubau crossing route with effective ship speed